2020
DOI: 10.1016/j.ekir.2020.02.913
|View full text |Cite
|
Sign up to set email alerts
|

Sun-374 B-Cell Depletion and Response in a Randomized, Controlled Trial of Obinutuzumab for Proliferative Lupus Nephritis

Abstract: Conclusions:The largest sample size to date is the strength of the study and we conclude CD-19 targeted rituximab is a safe and effective agent in the management of adults with SD/CNI dependent MCD/FSGS. At 12 months, over three-fourth of the patients with SD/CNI dependent podocytopathy maintain clinical remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Pre-clinical data showed the superior efficacy of obinutuzumab in B cell depletion compared with rituximab 24 . Recent results from the phase II NOBILITY study (NCT02550652) showed that obinutuzumab, when added to background immunosuppression comprising corticosteroids and mycophenolate, increased the rates of achieving primary and secondary efficacy endpoints, possibly related to a rapid and complete depletion of peripheral, memory, and naïve B cell subsets and plasmablasts 33 , 34 .…”
Section: Emerging Therapies Targeting B Lymphocytesmentioning
confidence: 99%
“…Pre-clinical data showed the superior efficacy of obinutuzumab in B cell depletion compared with rituximab 24 . Recent results from the phase II NOBILITY study (NCT02550652) showed that obinutuzumab, when added to background immunosuppression comprising corticosteroids and mycophenolate, increased the rates of achieving primary and secondary efficacy endpoints, possibly related to a rapid and complete depletion of peripheral, memory, and naïve B cell subsets and plasmablasts 33 , 34 .…”
Section: Emerging Therapies Targeting B Lymphocytesmentioning
confidence: 99%
“…Furthermore, a significant proportion of SLE patients (20% to 50%) are at risk of developing LN within the first year following their initial diagnosis of SLE [ 5 ]. Despite recent breakthroughs in the development of new therapeutics, it is crucial to acknowledge that the remission rate for LN remains low, from 30% to 70% [ 6 , 7 , 8 , 9 , 10 , 11 ]. This fact holds significant importance because achieving remission in LN is intricately linked to the risk of progressing to end-stage kidney disease (ESKD).…”
Section: Introductionmentioning
confidence: 99%